Effect of Chronic Hepatitis B Virus (HBV) Infection on Lipid Profile in Iraqi Patients - Amnah Raad Ibrahim; Athraa Zaidan Hassan; Raghad Hassan Hussein; Redhwan Abdul Kareem Alameer (Journal of Techniques)
Hepatitis B Virus (HBV) is known to target the liver, potentially leading to liver diseases. There's a notable link between dyslipidemia, an anomaly in lipid levels, and HBV infection. This research seeks to delve into the relationship between abnormal lipid profiles and HBV infection. The current study analyzed 90 participants; 50 of whom were patients with chronic HBV infection, and the remaining 40 were healthy individuals serving as the control group. Each participant took part in interviews and contributed blood samples for the analysis of their lipid profiles. The Cobas C 311 Roche System was employed to measure levels of HDL, cholesterol, LDL, triglyceride, and VLDL cholesterol, adhering to established lab protocols. The results showed that the HBV patient group had significantly elevated serum cholesterol, LDL, and triglyceride levels when compared to the healthy controls. Conversely, the HDL levels in the patient group were notably lower. Serum VLDL levels did not show any significant variation between the groups. The study identified altered lipid profiles in HBV patients, suggesting increased dyslipidemia and cardiovascular risks. Additional investigation is required to identify the root causes and suggest appropriate solutions.